Effects of Temperature and Pressure on Acute Stroke Incidence Assessed Using a Korean Nationwide Insurance Database - Jae-Sung Lim; Hyung-Min Kwon; Seong-Eun Kim; Juneyoung Lee; Young-Seok Lee; Byung-Woo Yoon (Journal of Stroke, 2017)
Background and Purpose Many studies have evaluated the association between weather and stroke, with variable conclusions. Herein we determined the relationships between daily meteorological parameters and acute stroke incidence in South Korea. Methods Patients with acute stroke (2,894) were identified by standard sampling of a nationwide insurance claims database from January to December 2011. We used multiple Poisson regression analyses of stroke incidence and meteorological parameters (mean temperature, diurnal temperature change, temperature differences over the preceding 24 hours, atmospheric pressure, humidity, wind speed, and physiologically equivalent temperature) to calculate the relative risk of stroke incidence associated with meteorological parameters. Results There were no seasonal variations in the incidences of ischemic (2,176) or hemorrhagic (718) stroke. Temperature change during the day was positively correlated with ischemic stroke in men (relative risk [RR] 1.027; 95% confidence interval [CI] 1.006–1.05) and older patients (≥65 years) (RR 1.031, 95% CI 1.011–1.052). Temperature differences over the preceding 24 hours had a negative correlation with all strokes (RR 0.968, 95% CI 0.941–0.996), especially among older women. Diurnal variation of atmospheric pressure was also significantly associated with the incidence of ischemic stroke (age<65 years, RR 1.051, 95% CI 1.011–1.092; age≥65 years, RR 0.966, 95% CI 0.936–0.997). Conclusions Diurnal temperature change, temperature differences over the preceding 24 hours, and diurnal variation of atmospheric pressure were associated with daily stroke incidence. These findings may enhance our understanding of the relationship between stroke and weather.